Neural Activation During Submaximal Contractions Seems More Reflective of Neuromuscular Ageing than Maximal Voluntary Activation - Scaglioni, Gil; Narici, Marco V.; Martin, Alain (Frontiers in Aging Neuroscience, 2016)
This study aimed at testing the hypothesis that differences in neural activation strategy during submaximal but not maximal plantarflexions exist between young and older men. Eleven young men (YM, 26±4 yr) and 13 OM (76±3 yr) volunteered for the investigation. Maximal voluntary torque (MVT) was 38.2%, lower (P<0.001) in OM than in YM, while voluntary activation was equivalent (~97%). The relationship between the interpolated twitch-torque and the voluntary torque (IT-VT relationship) was composite (curvilinear+exponential) for both age-groups. However, the OM showed accentuated concavity, as attested by the occurrence of the deviation from linearity at a lower contraction intensity (OM: 54.9 vs. YM: 71.9% MVT). In conclusion, ageing does not affect the capacity to fully activate the plantar flexors during maximal performances, but it alters the activation pattern for submaximal levels of effort. The greater age-related concavity of the IT-VT relationship suggests that, during submaximal contractions, OM need to reach a level of activation higher than YM to develop an equivalent relative torque.